Simulation Research for Grouping of Ammunition Dispersion Test With Monte-Carlo Method (Dandao Xuebao/Journal of Ballistics, 2023)
In order to reduce the cost of ammunition dispersion test and obtain the optimal number of bombs for dispersion test, the dispersion of the total number of certain ammunition in different grouping methods of grouping test and non-grouping test was simulated and calculated by Monte-Carlo method. The different test samples were simulated by different grouping methods and non-grouping methods. The average, variance and relative error of the estimated values of the overall dispersion were obtained, as well as the maximum, average and variance of the ratio of the maximum value to the minimum value in the dispersion of each group during the grouping test. The simulation results of group test were compared with those of the non-group test. The result shows that when the total number of test ammunition is fixed, the more the number of grouping, the larger the error of estimated dispersion, the worse the unbiasedness of the estimated value of dispersion, and the test without grouping can slightly improve the accuracy of the estimated dispersion, but the improvement is not obvious. In order to take into account the impact of random factors such as meteorology on the estimated dispersion, the dispersion test should be conducted in groups.